Occupational health risk assessment and health effects among workers in biogas palm oil plants, Sabah - Muhammad Najib Jaafar (2018)
Biagas is produced by a processing residual waste from palm oil mill effluents (POME) as well as waste water treatment plants. By constructing biogas plant in a palm oil mill, this POME is treated and turned out to be the main source of water without contributing to water pollution. However, biogas plant workers will be exposed to various hazards. Hydrogen sulphide gas and bio-aerosol dust are available in biogas plant which can cause health risks to the workers. Therefore, the aim of this study is to determine occupational health risks in biogas palm oil plant and respiratory health effects to the workers. This cross-sectional study was carried out to 200 workers of palm oil mill in Sabah and their health effects were compared between exposed and unexposed of biogas environment. All the biogas plants were evaluated and measured on the level of occupational health risk assessment (OHRA) by using two stage assessment methods namely initial assessment and detail assessment. Respondents were requested to fill up a standardized questionnaire, a physical examination, oximetry measurements and spirometry tests. Then, all the data collected were analysed by using SPSS software version 22. The OHRA conducted at biogas plants showed that all hazards categories namely physical, chemical, biological, psychosocial and ergonomic were present at medium risk score. The means of FVC and FEVl for exposed workers were 79.57% and 81.57%. The means of OHRA score by toxic gas and bio-aerosol dust were 11.89 (medium) and 5.68 (medium). Then, results of the Spearman's rho correlation showed that there is no significant correlation between respiratory health risk assessment by toxic gas and bio-aerosol dust with FVC, FEVl and FEVl/FVC. Meanwhile by comparing the exposed group and the unexposed group, there is a significant differences between biogas plant environment exposure and lung function test (LFT) result using Pearson Chi-square (p = 0.019, x2 = 5.51) with risk estimation in risk effect (OR = 1.96, 95% CI 1.12, 3.45). Regression analysis showed that duration of biogas plant operation was the most significant influence variable for respiratory health risk assessment scored by toxic gas and bio-aerosol dust. When the duration of biogas plant operation was longer, then the risk scores were also higher for both toxic and bio-aerosol risks. Thus, the working period of the respondents in biogas plant, is a significant influence variable for respiratory health effects. The biogas plant workers were two times at higher odds of being in abnormal lung function test compared to those workers in unexposed group. In addition, a worker who is active in sport or exercise is also a significant influence variable for respiratory health effect. Hence, the results of this assessment will be useful for manufacturers in planning and implementing optimal control measures to minimize the risks of respiratory diseases among the workers working at biogas plant environment.